Effect of proprioceptive neuromuscular facilitation and dynamic stretching on flexibility, agility, and balance in hamstring tightness among collegiate level badminton players - Hegishte, Atharva S.; Kumar, Neeraj (International Journal of Research in Medical Sciences, 2023)
Background: The development of muscular damage is typically attributed to intrinsic factors, such as muscle tension. Additionally, it has been demonstrated that muscular stiffness is the primary cause of the risk of pathological disorders of the knee and spine. Hamstring tightness leads to high risk of recurrent injury, decreases the performance in athletes, lead to post-exercise soreness and decreases coordination among athletes. Objectives of current study were to find out the effects of PNF and dynamic stretching on flexibility, balance, and agility among collegiate level badminton players having hamstring tightness. Methods: 110 participants were screened and 68 participants were recruited according to the selection criteria and were randomly allocated to Group A (PNF stretching) (N=34) and Group B (Dynamic Stretching) (N=34). The exercise program underwent training for 30 min, 3 times per week for 4 weeks. Results: Group A and Group B demonstrated significant improvement in Flexibility, Balance, and Agility (p<0.0001). Whereas, no significant difference was seen when intergroup comparison was done (p>0.005). Conclusions: The study concludes that there is significant improvement in the Flexibility, Balance, and Agility after implication of 4 weeks of PNF and Dynamic Stretching in Collegiate Level Badminton players having Hamstring tightness. This evidence substantiates that these exercises do recruit the Hamstring muscles and provides further insight into the role of the Hamstring muscles to keep the body flexible.